Factors Affecting the Ups and Downs of Profit in the Food and Beverage Sub-Sector for the 2021-2023 Period - Dewi, Nurul Aulia; Rossalina, Zahra; Budianto, Erwin (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The purpose of this study is to ascertain how production and sales rates, and sales growth relate to changes in net profit between 2021 and 2023. Design/methodology/approach: This study used a quantitative descriptive strategy, with purposive sampling as a technique for selecting samples based on certain criteria, and the study population consisted of 18 organizations. Information was obtained from financial reports accessed on the website www.idx.co.id. Findings: According to this analysis, the factors of sales growth, production costs, and operating costs have a major impact on the amount of money businesses in the food and beverage subsector make between 2021 and 2023. Research limitations/implications: The scope of this study is limited to food and beverage subsector companies listed for 3 years on the IDX. In addition, the focus of activities are only factors that affect sales growth, production costs, and operating costs. Practical implications: Can make plans to improve profitability using the findings of the research analysis. Originality/value: This paper is original Paper type: Research paper